Preparation and in vitro evaluation of folate-receptor-targeted SPION-polymer micelle hybrids for MRI contrast enhancement in cancer imaging - Mahajan, Shveta; Koul, Veena; Choudhary, Veena; Shishodia, Gauri; Bharti, Alok C (Nanotechnology, 2013)
Polymer-SPION hybrids were investigated for receptor-mediated localization in tumour tissue. Superparamagnetic iron oxide nanoparticles (SPIONs) prepared by high-temperature decomposition of iron acetylacetonate were monodisperse (9.27 ± 3.37 nm), with high saturation magnetization of 76.8 emu g(-1). Amphiphilic copolymers prepared from methyl methacrylate and PEG methacrylate by atom transfer radical polymerization were conjugated with folic acid (for folate-receptor specificity). The folate-conjugated polymer had a low critical micellar concentration (0.4 mg l(-1)), indicating stability of the micellar formulation. SPION-polymeric micelle clusters were prepared by desolvation of the SPION dispersion/polymer solution in water. Magnetic resonance imaging of the formulation revealed very good contrast enhancement, with transverse (T(2)) relaxivity of 260.4 mM(-1) s(-1). The biological evaluation of the SPION micelles included cellular viability assay (MTT) and uptake in HeLa cells. These studies demonstrated the potential use of these nanoplatforms for imaging and targeting.